2D kaolin ultrafiltration membrane with ultrahigh flux for water purification. (1st June 2019) - Liu, Ting; Zhou, Huimin; Graham, Nigel; Yu, Wenzheng; Sun, Kening
Abstract: Membrane separation technology is an important option for the treatment of contaminated surface waters but the relatively high cost of materials and membrane fabrication represent a significant obstacle to the wider use of membrane processes. In this study, we describe the development and testing of a new kind of membrane made from two-dimensional (2D) kaolin nanosheets. The fabrication involved a layer-by-layer stacking of the nanosheets with a cationic polyacrylamide cross-linking agent, assembled on a cellulose acetate supporting layer. The kaolin membrane exhibited an ultrahigh flux (∼4000 L.m- 2 .h −1 .bar −1 ) which was almost ten times greater than that of a commercial polyether sulfone (PES) ultrafiltration (UF) membrane. The membrane was tested using a range of influent water types, including samples of a lake water, river water and three natural organic matter solutions. The results showed that the kaolin membrane was stable and behaved as an UF membrane, in terms of its pore size distribution (peak distribution at 20–35 nm) and comparable treatment performance to the PES UF membrane. The kaolin membrane showed a substantially reduced rate of fouling, compared to PES membrane, despite a much greater flux, which was partly attributed to its highly hydrophilic nature. The advantages of lower cost, much higher flux and lower fouling propensity make the 2D-kaolin membrane a potentially important development in UF membrane technology for drinking water treatment, and possibly other applications. Graphical abstract: Image 1 Highlights: A stable and cost-effective 2D-kaolin UF membrane is fabricated. The fabrication involved a stacking of kaolin nanosheets cross-linked with CPAM. It exhibited an ultrahigh flux compared to the commercial PES UF membrane. The antifouling performance of the membrane was superior for the NOM foulants.